2004
DOI: 10.1016/s1573-5214(04)80006-x
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter and Salmonella infections on organic broiler farms

Abstract: Organic poultry production in the Netherlands is developing. Although consumers assume organic products to be safer and healthier, there are aspects of organic animal husbandry, like access to an outdoor run, that can result in increased risks of food safety problems. The aim of this study was to compare housing and management of organic and conventional broiler farms in the Netherlands and to study the occurrence of Salmonella and Campylobacter infections on the former. Large differences were found between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 12 publications
3
17
0
Order By: Relevance
“…However, it must be noted that only a limited number of flocks was investigated in our study. In a larger study conducted in the Netherlands between 2001 and 2003, the estimated flock prevalence of Campylobacter in organic systems ranged between 35 and 65% and of Salmonella between five and 13% (Rodenburg et al, 2004a;Van Der Hulst-Van Arkel et al, 2004). These results agree with our finding that, at least in this part of Europe, Campylobacter is an important hygiene and food safety concern in organic broiler farming.…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be noted that only a limited number of flocks was investigated in our study. In a larger study conducted in the Netherlands between 2001 and 2003, the estimated flock prevalence of Campylobacter in organic systems ranged between 35 and 65% and of Salmonella between five and 13% (Rodenburg et al, 2004a;Van Der Hulst-Van Arkel et al, 2004). These results agree with our finding that, at least in this part of Europe, Campylobacter is an important hygiene and food safety concern in organic broiler farming.…”
Section: Discussionmentioning
confidence: 99%
“…63,64 It has been shown that rodent control measures can effectively decrease S. enteritidis in the hen house. 21,65,66 In one study, 100 conventional flocks were monitored for one production cycle to investigate risk factors for Campylobacter infection of broiler flocks. 13 The authors did not encounter evidence of environmental survival of Campylobacter in broiler houses after adequate cleansing and disinfection.…”
Section: Importance Of Rodent Controlmentioning
confidence: 99%
“…Henzler et al (1998) demonstrated the direct association between the presence of rats and poultry diseases because they documented that effective control measure of rodents in the poultry house resulted in reduced bacterial infection of the associated poultry. It has also been shown that rodent control measures can effectively decrease Salmonella species in poultry houses (Rodenburg et al, 2004). Rats are common commensal pest (Meerburg et al, 2009), which can damage the food products, buildings, stored products, and also serve as potential vector of pathogenic diseases in human and animals.…”
Section: Introductionmentioning
confidence: 99%